Accounting for Growth in Spain, 1850-2019 - Leandro Prados de la Escosura; Joan R. Rosés (European Historical Economics Society (EHES), 2020)
The current productivity slowdown has stimulated research on the causes of growth. We investigate here the proximate determinants of long-term growth in Spain. Over the last 170 years output per hour worked raised nearly 24-fold dominating GDP growth, while hours worked per person shrank by one-fourth and population trebled. Half of labour productivity growth resulted from capital deepening, one-third from total factor productivity, and labour quality contributed the rest. In phases of acceleration (the 1920s and 1954-85), TFP was labour productivity's main driver complemented by capital deepening. Since Spain's accession to the European Union (1985), labour productivity has sharply decelerated as capital deepening slowed down and TFP stagnated. Up to the Global Financial Crisis (2008) GDP growth mainly resulted from an increase in hours worked per person and, to a less extent, from sluggish labour productivity coming mostly from weak capital deepening. Institutional constraints help explain the labour productivity slowdown.
Keywords: D24; E01; O47; N13; N14; 330; Growth; Labour Productivity; Capital Deepening; Labour Quality; Total Factor Productivity; Spain